2017
DOI: 10.1071/rd15334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum oilseed supplements on subclinical endometritis, pro- and anti-inflammatory cytokine transcripts in endometrial cells and postpartum ovarian function in dairy cows

Abstract: Abstract. Postpartum uterine infections affect ovarian function and delay ovulation in cattle. As dietary fats can affect immune cell function, we investigated the influence of prepartum diets on postpartum uterine inflammatory status (UIS) as assessed 25 AE 1 days postpartum by endometrial cytology (normal: #8% polymorphonuclear cells (PMN) vs subclinical endometritis (SCE): .8% PMN) and associations between SCE, pro-and anti-inflammatory cytokine gene expression and ovarian function. During the last 5 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
6
0
1
Order By: Relevance
“…Similar findings were reported by Galvão, Santos, Galvão, and Gilbert () and Salehi et al. () who also found an increase in IL1B , TNF and CXCL8 relative mRNA expression in endometrial of cows with subclinical endometritis compared to healthy cows. Endometrial mRNA expression of TNF, IL1B and CXCL8 was upregulated in response to an i.u.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar findings were reported by Galvão, Santos, Galvão, and Gilbert () and Salehi et al. () who also found an increase in IL1B , TNF and CXCL8 relative mRNA expression in endometrial of cows with subclinical endometritis compared to healthy cows. Endometrial mRNA expression of TNF, IL1B and CXCL8 was upregulated in response to an i.u.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with earlier findings that the increased mRNA expression of IL1B and CXCL8 was related to the severity of uterine inflammation (Peter et al, 2015). Similar findings were reported by Galvão, Santos, Galvão, and Gilbert (2011) and Salehi et al (2017) who also found an increase in IL1B, TNF and CXCL8 relative mRNA expression in endometrial of cows with subclinical endometritis compared to healthy cows. Endometrial mRNA expression of TNF, IL1B and CXCL8 was upregulated in response to an i.u.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Calcium, Mo, P, Se, and Zn were lesser in cows with metritis and Ca, Cu, Mo, and Zn were lesser in cows with SCE compared with healthy cows (Bicalho et al, 2014b). Salehi et al (2016) found greater expression of genes associated with inflammation in cows with SCE (IL1B, IL8, IL10) and TNFα but did not find any differences when healthy and SCE cows were supplemented with oilseeds which are recognized to suppress inflammation. Other supplements such as monensin and high starch diets improved the activity of immune cells (PMN, phagocytes, and monocytes), but they did not improve uterine health in cows with SCE diagnosed by uterine lavage at 8 and 47 DIM.…”
Section: Risk Factors Associated With Uterine Disease Nutritional Andmentioning
confidence: 71%
“…The same effect was seen for SCE (> 8% PMN at 25 DIM). Cows with SCE had delayed resumption of ovarian activity after calving (Salehi et al, 2016). Some studies have examined the effects of uterine disease on ovarian structures and associated hormones.…”
Section: Effects Of Uterine Disease On Ovarian Structures and Their Pmentioning
confidence: 99%